Wave and wave-current actions on a bridge tower: An experimental study. Issue 6 (April 2019) - Wei, Chengxun; Zhou, Daocheng; Ou, Jinping
With a scale of 1:100, an experimental model was set up to investigate the dynamic responses of a bridge tower subjected to ocean waves and wave-currents. The bridge tower was designed for a sea-crossing bridge. Based on a pile-group foundation, it was designed to be a typical gate-type structure. Wave-induced base shear forces on the foundation and motion responses of the tower were measured and analyzed. The experimental results show that when a wave period is close to the natural period of the structure, an obvious resonance will be induced on the structure. For different wave action angles, the longitudinal incident waves induced the largest longitudinal base shear forces on the foundation and the greatest dynamic motions on the upper tower of the structure. Because of the pile-group effectiveness, the incident directions of the waves and the wave periods affect the acting forces on the foundation of the structure. For wave-current actions, forward currents increase the forward wave forces on the foundation and decrease the backward forces, but do not significantly affect the motion responses of the upper tower. The experimental results can be used as the verification data for numerical calculations. With the structural forms of the pile-group and the gate-type tower being typical, the results given in this study can be used as a reference for similar engineering designs.